Congenital myasthenic syndromes: A study of 15 cases. Issue 3 (6th February 2023) - Khadilkar, Satish V.; Oza, Harsh; Dhonde, Pramod; Patel, Bhagyadhan; Singla, Madhu bala; Patel, Riddhi; Dastur, Rashna; Gaitode, Pradnya; Halani, Hiral; Mansukhani, Khushnuma; Dhonde, Mayura
Abstract: Background: Congenital myasthenic syndromes (CMS) are rare inherited heterogeneous disorders of neuromuscular transmission. Aims and methodology: This study aims to describe clinical and investigative characteristics including genetic aspects of patients with congenital myasthenic syndrome (CMS), in a cohort from western India. Retrospective analysis for the study period of 9 years (−January 2013 to December 2021) was performed. Patients were identified by predefined selection criteria using a combination of clinical, electrophysiological, and genetic studies. Results: Fifteen genetically evaluated CMS patients, 11 females, and 4 males were identified. Ten patients had a history of fatigable ptosis at an early age, whereas all patients had varying degrees of proximal weakness at the time of presentation. The mean age at onset was 16 years and the mean age at final diagnosis was 22 years, thereby representing a mean delay in diagnosis of 6 years. Among the total 13 different genetic mutations identified, 4 are not previously reported. The most common genetic mutations identified were CHRNE gene (in 7 patients) followed by DOK7 gene ( in 6 patients), and the remaining 2 patients had mutation in MUSK gene. Roma founder mutation (c.1327delG, p.E443ter) was seen in 5 patients with CHRNE gene. Four patients responded to pyridostigmine alone, 7 patients to salbutamol, whereas 4 patients required a combination of pyridostigmine and salbutamol. Conclusion: This study, carried out in a small cohort of patients, highlights the frequent occurrence of Roma founder mutation in our population, and the predominance of CHRNE and DOK7 gene mutations, points of regional importance. Four novel variants were also identified in the genetic studies carried out.